Uji Aktivitas Penghambatan Xantin Oksidase secara In-Vitro oleh Isolat 6,4’-Dihidroksi-4-Metoksibenzofenon-2-O-β-D Glukopiranosida(C20H22O10) yang Diisolasi dari Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl) - Rina Yanti Eff, Aprilita; Rahayu, Sri Teguh; Syachfitri, Resta Dwi (UI Scholars Hub, 2016)
Hyperuricemia is a condition in which an increasing in uric acid levels abovenormal. Hyperuricemia is a major factor in the development of gout. Gout is adisease caused by the accumulation of monosodium urate crystals in the tissues dueto elevated levels of uric acid. Crown gods (Phaleria macrocarpa (Scheff.) Boerl) is Indonesia native medicinal that has effect such as lowering blood pressure, diabetes mellitus drugand lowering uric acid levels. One of the chemical constituents of this plant is abenzopheneon compound that is 6,4’-dihydroxy-4-metoksi benzofenon-2-O-β-D-glukopiranosida (C20H22O10). Research was conducted to determine the activity of 6,4’-dihydroxy -4-metoksi benzofenon-2-O-β-D-glukopiranosida (C20H22O10) that isolated from Crown gods in inhibiting xanthine oxidase by in-vitro method using spechtrofotometer with allopurinol as a positive control.The results showed that isolates 6,4’-dihydroxy-4-metoksi benzofenon-2-O-β-D-glukopiranosida (C20H22O10) has inhibitory activity against xanthine oxidase with IC50 values 15.705 mg / mL. However, allopurinol has xanthine oxidase inhibitory activity higher than isolates with IC50value of 0.091 mg/mL. Lineweaver-Burk plot showed that isolates 6,4’-dihydroxy-4-metoksi benzofenon-2-O-β-D-glukopiranosida(C20H22O10) has a competitive inhibitory activity.